Electromagnetic, flow and thermal coupling in a MHD pump taking account the saturation of the ferromagnetic material - FZ. Kadid; MS. Aggoune; S. Drid (Eleventh International Conference on Ecological Vehicles and Renewable Energies (EVER’16)EVER’2016, 2016)
This paper deals with robust direct power control of a grid-connected brushless doubly-fed induction generator(BDFIG). Using a nonlinear feedback linearization strategy, an attempt is made to improve the desired performances by controlling the generated stator active and reactive power in a linear and decoupled manner. Therefore, to achieve this objective, the Lyapunov approach is used associated with a sliding mode control to guarantee the global asymptotical stability. Thus, an optimal operation of the BDFIG in sub-synchronous operation is obtained as well as the stator power flows with the possibility of keeping stator power factor at a unity. The proposed method is tested with the Matlab/Simulink software. Simulation results illustrate the performances and the feasibility of the designed control.